Association of diabetes mellitus and breast cancer in adult men and women: a cross-sectional survey - Rabiya Saroosh; Nazir Ahmad; Beenish Israr; Anum Nazir; Nizwa Itrat; Abdul Momin Rizwan Ahmad (BMC Cancer)
Abstract Background The co-occurrence of diabetes mellitus and breast cancer poses a significant global health challenge. Most research has focused on Western populations, with genetics, lifestyle, and environmental differences limiting generalizability to Pakistanis. This study aimed to fill this gap by investigating the diabetes-breast cancer association among Pakistani adults. Methods A cross-sectional study was conducted from October 2023 to January 2024 at Pinum Cancer Hospital, Faisalabad. 400 participants were categorized as normal, diabetic, cancerous, and diabetic cancerous. Data were analyzed using SPSS with descriptive statistics and inferential tests at p < 0.05 significance. Results Among 9,725 patients, 1.03% had concurrent diabetes and breast cancer. Females showed higher risk with a strong gender association (P < 0.0001) across groups. Significant associations were found for body weight (P < 0.009), BMI (P < 0.014), and fat distribution (P < 0.0001). Dietary factors such as fried fish (P < 0.001), red meat (P < 0.0001), processed food (P < 0.0001), and kitchen practices like overcooked oil (P < 0.003) were significant. Lifestyle factors including physical activity (P < 0.0001) and stress (P < 0.0001), environmental factors such as x-rays, and chemical exposure (P < 0.013) and female-specific factors like postmenopausal status (P < 0.0001) and contraceptive use (p < 0.032), and makeup (P < 0.0001) also showed significant association. Conclusion Diabetes and breast cancer are strongly associated in Pakistani adults, influenced by clinical, dietary, lifestyle, and environmental factors. Personalized prevention and management strategies are crucial to improve treatment outcomes.